Multistate Outbreaks of Foodborne Illness in the United States Associated With Fresh Produce From 2010 to 2017 - Carstens, Christina K.; Salazar, Joelle K.; Darkoh, Charles (Frontiers in Microbiology, 2019)
In the United States, the consumption of fresh fruits and vegetables has increased during recent years as consumers seek to make healthier lifestyle choices. However, the number of outbreaks associated with fresh produce that involve cases in more than one state (multistate) has increased concomitantly. As the distance along the farm-to-fork continuum has lengthened over time, there are also more opportunities for fresh produce contamination with bacterial pathogens before it reaches the consumer. This review provides an overview of the three bacterial pathogens (i.e., pathogenic Escherichia coli, Listeria monocytogenes, and Salmonella enterica) associated with multistate fresh produce outbreaks that occurred between 2010 and 2017 in the U.S. Possible routes of fresh produce contamination, including pre- and post-harvest, are summarized and outcomes of selected outbreaks within this timeframe are highlighted. Eighty-five multistate outbreaks linked to fresh produce with a confirmed etiology occurred from 2010 to 2017. Cross-contamination within the distribution chain and poor agricultural practice, along with the production of sprouts and importation of fresh produce were frequently implicated contributors to these events. The evolution of the food supply in the U.S. necessitates an examination of multistate outbreaks to shed light on factors that increase the scale of these events.